Computations of local nonsimilar solutions for MHD flow of Reiner–Rivlin fluid - Khan, Sohail A.; Hayat, Tasawar; Alsaedi, Ahmed; Momani, Shaher (Nonlinear Analysis: Modelling and Control, 2025)
Here local nonsimilar solution for hydromagnetic stretched flow of Reiner–Rivlin material is constructed. Heat generation, radiation, and dissipation in thermal expression are studied. Joule heating and chemical reaction of first order are under consideration. Entropy generation is computed. Nonlinear system is derived by adequate transformations. Optimal homotopy analysis technique computes the analysis. Attention is focused to achieve the results of concentration, fluid flow, entropy rate, and temperature. In addition, the skin friction, solutal transport rate and Nusselt number have been explained. Outcomes of magnetic field on velocity and entropy rate are found opposite. Large approximation of fluid parameter improves the fluid flow. Larger estimation of Brinkman number yields same results of entropy generation and temperature. Reduction in concentration is noted through Schmidt number. Higher reaction variable correspond to reduce concentration. Temperature and entropy generation through radiation variable has similar trend. Material variable has similar results for rate of mass transport and coefficient of skin friction. Radiation amplifies the thermal transport rate. Reverse effect for entropy rate and Bejan number is detected for magnetic field.